Resposta estratégica às mudanças climáticas globais: o caso de duas multinacionais do setor de alumínio - Cunha, Larissa Teixeira da (2012)
Climate change as a global issue in its causes and consequences require international cooperation and leadership. In this context, multinational corporations play a special role as they operate globally and deal with various issues, actors and institutional contexts. The greatest climate challenge for companies refers to the ability to reduce costs and risks related to their business, what can be achieved through the development of a broad and clear strategy able to face the transition to a low carbon market and gather new and unique opportunities. Thus, this work aims to identify and compare the strategic responses to global climate change of two multinational corporations in the aluminum industry taking into account their subsidiaries, one located in Canada and the other in Brazil. Hence, we developed a conceptual framework addressing the main drivers (establishment and development of regulations, competitive requirements and public perception) and steps (business exposure to carbon, taking action – market strategies, and influencing the policy development process – political strategies) involved in the building process of climate strategies by a corporation. The methodology used in this paper refers to a multiple case study involving two corporations in the aluminum industry (MNC-A e MNC-B) taking into account their subsidiaries in Canada (MNC-ACan) and Brazil (MNC-BBra). The strategic responses to climate change of these corporations were analyzed and described using the pattern matching technique and subsequently compared using the cross-case syntheses technique. The study concludes that climate change is still an uncertain and conflicting issue regarding the performance of companies and governments. The regulatory environment appears as a potential driver, compromised by political uncertainties at international and mainly national levels, hence allowing highly discretionary actions by companies. In this context of lacking clear and enforceable standards, the market environment predominates, favoring the compliance with competitive requisites, such as cost and efficiency improvement.